(NbLUVDA@]IE ZWEZDY(B: [(NrOMAN(B] / s (N~ASTX (B2s - (N{OLOM(B-(NaLEJHEMs ((NmOSKWA(B: s (NgOSUDARSTWENNOE IZDATELXSTWO HUDOVESTWENNOJ LITERATURY(B, s, 1959)
(NwO WTOROJ TOM WO[EL ROMAN (B"(NbLUVDA@]IE ZWEZDY(B".s
rus
Keywords: (NpSIHOLOGI^ESKIJ ROMANs; (NsOCIALXNO(B-(NPSIHOLOGI^ESKIJ ROMANs